PENGARUH PEMBAYARAN NON TUNAI TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA TAHUN 2011-2021: PENGARUH PEMBAYARAN NON TUNAI TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA TAHUN 2011-2021 - Keke Oktavia (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2023)
Abstract. This study aims to examine the effect of non-cash payments on economic growth in Indonesia in the most recent period. The independent variables in this study are debit/ATM cards, credit cards and e-money. The data in this study is secondary data obtained directly from the Central Bureau of Statistics and Bank Indonesia from 2011 to 2021. In this study, Eviews 9 was used. The results of this study indicate that debit/ATM cards, credit cards and e-money have a significant effect on economic growth. in Indonesia. Debit/ATM cards have a significant effect on economic growth, credit cards have a significant effect on economic growth, E-money does not have a significant effect on economic growth where the JB prob Normality test results test is calculated at 0.556338 > 0.05, meaning that normality has been fulfilled, multicollinearity test Using the correlation matrix, multicollinearity did not occur. The results of the Heteroscedasticity test calculated the prob-f value of 0.2520 > 0.05, meaning that there was no heteroscedasticity. The results of the multiple linear regression test were used to observe a relationship between the x and y variables. the results of the t test show that x1 has a significant effect x2 has a significant effect while x3 has no significant effect, F test 0.013857 <f table means H4 is accepted.Keywords: Non-Cash Transactions, Debit/ATM Cards, Credit Cards, E-Money, Economic Growt